Effectiveness of Audiovisual Media vs Leaflets in Improving Mothers' Knowledge of Diphtheria in Toddlers in Mojo Health Center, Surabaya - Enung Mardiyana Hidayat; Zakiyyatus Salsabilah; Miadi; Adin Mu`'afiro (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Diphtheria is a contagious disease that can lead to airway obstruction and death. Maternal knowledge about diphtheria is crucial for preventing the disease, and health education is essential in increasing this knowledge. This study aims to compare the effectiveness of health education through audiovisual media and leaflets in improving maternal knowledge about diphtheria in children under five years of age in the working area of Mojo Health Center, Surabaya.This research used a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 198 mothers of children aged 1-5 years at Posyandu Kartini 12 Jojoran, selected through cluster random sampling. The independent variables were the type of health education delivered through audiovisual media and leaflets, while the dependent variable was maternal knowledge regarding diphtheria, measured using a questionnaire. The data were analyzed using the Wilcoxon and Mann-Whitney tests. The mothers' knowledge before receiving health education using audiovisual media was mostly inadequate 60%. However, after the education, there was a significant improvement, with 76% showing good knowledge, with a p-value of 0.000. Similarly, before health education using leaflets, the majority 58% had inadequate knowledge, but after the education, most 59% showed sufficient knowledge, with a p-value of 0.000, as analyzed using the Wilcoxon test. The results showed that audiovisual media was more effective in improving mothers' knowledge compared to leaflets, with a p-value of 0.000 in the Mann-Whitney test. Health education using audiovisual media and leaflets significantly improves maternal knowledge. Audiovisual media proved to be more effective in enhancing maternal knowledge about diphtheria in children under five years of age at Mojo Health Center, Surabaya.